Hudebni dovednosti ucitele pohledem pedagogu materskych skol - prvni vysledky vyzkumneho setreni - Kmentova, Milena; Chumchal, Jan; Loudova Stralczynska, Barbora; Jindrova, Barbora (Aura musica, 2025)
This paper presents the preliminary findings of a study aimed at identifying the musical competencies essential for music education in pre-school settings, as perceived by pre-school educators. The objective was to gather insights into the perspectives of pre-school teachers regarding the requisite skills for effectively fostering musical development of young children. The data obtained will support the innovation of educational programmes. They will be a source for the creation of new didactic materials designed for the teaching of didactically oriented music education subjects at the level of bachelor studies and vocational upper secondary education in pre-school and out-of-school pedagogy. The research indicates that contemporary pre-school educators possess a comprehensive understanding and hold high expectations for graduates of relevant study programs in terms of musical literacy and music- didactic competencies.
Keywords: Music education; teacher preparation; pre-primary education; music education research